Short communication: A new minicurd model system for hard cooked cheeses - Vélez, María Ayelén (2015)
The aim of this study was to propose and validate a new minicurd model of young hard cheese. Curd particles and whey obtained from conventional cheese making of Reggianito Argentino were separated and frozen. Then, both fractions were thawed and the mixture of whey and curds was reconstituted, from which minicurds were made on the laboratory scale. Repeatability and the effect of freezing on minicurd composition were investigated by assessing pH, protein and moisture contents, sodium chloride content, and total thermophilic lactic flora counts. Good repeatability was achieved, and no significant differences were found between minicurds made from fresh compared with frozen materials. Composition of the minicurd was appropriate for modeling Reggianito Argentino cheese.